History and hope in the heart of Dixie : scholarship, activism, and Wayne Flynt in the modern South - Harvey, Gordon E. (Gordon Earl), 1967-; Starnes, Richard D., 1970-; Feldman, Glenn (Modern South., 2006)
Social and political history of the modern South. This collection of essays on the social and political history of the modern South consider the region's poor, racial mores and race relations, economic opportunity, Protestant activism, political coalitions and interest groups, social justice, and progressive reform. History and Hope in the Heart of Dixie illuminates the dual role of historian and public advocate in modern America. In a time when the nation's eyes have been focused by Hurricanes Katrina and Rita onto the vulnerability and dire condition of poor people in the South.